1998
DOI: 10.17129/botsci.1571
|View full text |Cite
|
Sign up to set email alerts
|

Florística del bosque mesófilo de montaña de Molocotlán, Molango-Xochicoatlán, Hidalgo, México

Abstract: He rba ri o FCME, Departamento de Bio logía, Facultad de Ciencias, Univ ersidad Nac ional Autónoma de Méx ico, Ciudad Universitari a, Apartado Po stal 70-39 9, Méx ico 04510, D.F., Méx ico . e-mail : il v@ hp.fcie ncias .un am.m x Resumen . El bo squ e m esófil o ele Mol ocotlán a barca parte ele d os muni cipi os del es tad o el e Hid algo, Mo la ngo y Xochi coatl á n , a mb os enclavados d e nt ro ele la Sierra Madre O rie n ta l, e n la Hu asteca Hi cla lg ue nse . El bosqu e prese nta tres es tratos a rbór… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…Other plant species that are also known to be associated with riparian zones in cloud forest include Deppea grandiflora, Boehmeria caudata, S. glabrescens, and A. acuminata (Mayorga et al 1998, Gual-Díaz & Rendón-Correa 2014, all of which were found in this study. Trees of different species of Quercus are also abundant in riparian zones as well as in sites far away from rivers, being one of the most important genus of trees in cloud forest of Mexico and Central America (Johnson & Jones 1977, Granados-Sánchez et al 2006, Nur et al 2008.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Other plant species that are also known to be associated with riparian zones in cloud forest include Deppea grandiflora, Boehmeria caudata, S. glabrescens, and A. acuminata (Mayorga et al 1998, Gual-Díaz & Rendón-Correa 2014, all of which were found in this study. Trees of different species of Quercus are also abundant in riparian zones as well as in sites far away from rivers, being one of the most important genus of trees in cloud forest of Mexico and Central America (Johnson & Jones 1977, Granados-Sánchez et al 2006, Nur et al 2008.…”
Section: Discussionsupporting
confidence: 53%
“…While for the same area but within cloud forest remnant fragments of 1.2 up to 40 ha, Toledo-Aceves et al (2014) found 45 tree species in 0.48 of sampling area and Williams-Linera (2002) found 71 tree and 24 shrub species in 0.7 ha of sampling area. In other states of the country with cloud forest, different studies have reported between 76 and 121 tree species and 59 to 151 shrub species (Mayorga et al 1998, Alcántara-Ayala & Luna-Vega 2001, Cartujano et al 2002, reaching 300 or more species of woody plants in some regions (Ramírez-Marcial 2001), albeit these studies covered larger areas and were carried out mostly in well preserved cloud forest. For the case of riparian habitats, other studies have found between 34 to 70 tree species and 33 to 49 shrub species in sampling areas ranging from 0.2 up to 1 ha, although these studies were carried out in deciduous oak forest of Morelos (Camacho-Rico et al 2006) and tropical rain forest in SE Mexico (Moreno-Jiménez et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En el estado de Hidalgo se han realizado algunos estudios sobre flora vascular en general en varios municipios con BMM (Luna-Vega et al 1994, Alcántara-Ayala & Luna-Vega 1997, 2001, Mayorga et al 1998, Ponce-Vargas et al 2006, donde se destaca la elevada riqueza de pteridobiontes. Además, existen varios trabajos en el BMM enfocados a conocer la composición de pteridobiontes en los municipios de Calnali (Pérez-Cervantes 2009), San Bartolo Tutotepec (Gutiérrez-Lozano et al 2017), Tenango de Doria (Zúñiga-Salvatierra 2009), Tlanchinol (Álvarez-Zúñiga et al 2012) y Zacualtipán de Ángeles (Pérez-Paredes et al 2012).…”
Section: Materiales Y Métodosunclassified
“…La mayoría de los estudios descriptivos realizados en México para estas comunidades de montaña se han enfocado hacia aspectos de su composición florísitica (e.g. Luna et al, 1988;Luna et al, 1989;Puig, 1989;Luna et al, 1994;Rzedowski, 1996;Alcántara-Ayala y Luna-Vega, 1997;Mayorga-Saucedo et al, 1998) . Además, los estudios en los que se describen su fisonomía y estructura (e.g.…”
unclassified